A new interpretation of the common heritage of mankind in the context of the international law of the sea. (15th June 2020) - Wang, Chuanliang; Chang, Yen-Chiang
Abstract: After Arvid Pardo recommended that the seabed and subsoil beyond national jurisdiction should be regarded as Common Heritage of Mankind (hereinafter CHM), put forward the proposal of an international seabed system, the principle of CHM was perceived as the foundation of a specific marine legal regime. Later, the principle of CHM was stipulated, both in the General Assembly Resolution 2749 (XXV) and UNCLOS. However, there is no clear definition of its legal connotations. This paper analyzes the legal connotation of CHM by reviewing relevant international legal documents. In the context of the international law of the sea, the legal connotations of CHM are as follows: the subject of CHM is the aggregation of all States. Marine resources, which are seen as CHM, have the characteristics of extraterritoriality, sharing and legality. There are four main elements of CHM based on content elements considered: Firstly, no State shall claim or exercise sovereignty or sovereign rights over marine resources, which are seen as CHM, nor shall any State or natural or juridical person appropriate any part thereof. Secondly, it must be used for the benefit of all mankind, taking into account the interests and needs of developing States in particular. Thirdly, it must be used exclusively for peaceful purposes. Fourthly, take into account the protection of the marine environment and the sustainable use of marine resources. With the modification and refinement of the Area system, the connotations of CHM have been evolving. The principle of CHM can provide theoretical basis for some marine management approaches which is of significance for current and future international law-making and can lay the foundation for new regimes of international law of the sea in the future. Graphical abstract: Image 1 Highlights: UNCLOS and the 1994 Implementation Agreement established the Area system based on the principle of CHM. The subject of CHM is the aggregation of all States. CHM has the characteristics of extraterritoriality, sharing and legality. The principle of CHM can provide theoretical basis for marine management approaches and lay the foundation for the law of the sea.